New frontiers of trade and trade policy: digitalization and climate change. (7th February 2023) - Jones, Emily; Adam, Christopher
Abstract: The global spread of the digital revolution and the need to manage the climate have radically altered the international trade landscape and have rendered the architecture of the World Trade Organization ill-equipped to address emerging regulatory challenges posed by cross-border flows of digital products and by carbon emissions embodied in traded goods and services. This essay reviews the set of papers published in this issue of the Oxford Review of Economic Policy that assess the regulatory challenges presented by these two 'new frontiers' of trade and evaluate alternative national and supranational trade and industrial policy responses.